Pengembangan Media Ajar IPAS Melalui Aplikasi Assemblr Edu Untuk Meningkatkan Keterampilan Proses Sains Di Min 2 Langsa - Desy Yunita; Jelita; Nur Balqis Mutia (Jurnal Ilmu Pendidikan, 2026)
This study aimed to determine the feasibility, practicality, and effectiveness of IPAS learning media based on the Assemblr Edu application in improving the science process skills of fifth-grade students at MIN 2 Langsa. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 30 fifth-grade students of MIN 2 Langsa. Data collection techniques included material expert validation, media expert validation, language expert validation, student response questionnaires, pretest and posttest, and observation sheets. The data were analyzed using percentage analysis to determine the feasibility and practicality of the media, while the effectiveness of the media was analyzed using the Wilcoxon Signed Rank Test. The results showed that the Assemblr Edu-based IPAS learning media obtained an average validation percentage of 96%, categorized as highly feasible. Student response questionnaires showed a percentage of 90.27%, categorized as highly practical. The Wilcoxon test result showed a significance value of < 0.001, indicating that the media was effective in learning activities. In addition, the observation results of students’ science process skills obtained a percentage of 96% with a very good category. Therefore, the IPAS learning media through the Assemblr Edu application is feasible, practical, and effective in improving students’ science process skills on ecosystem material.